Dissecting weed adaptation: Fitness and trait correlations in herbicide‐resistant Alopecurus myosuroides. Issue 7 (9th May 2022) - Comont, David; MacGregor, Dana R; Crook, Laura; Hull, Richard; Nguyen, Lieselot; Freckleton, Robert P; Childs, Dylan Z; Neve, Paul
Abstract: BACKGROUND: Unravelling the genetic architecture of non‐target‐site resistance (NTSR) traits in weed populations can inform questions about the inheritance, trade‐offs and fitness costs associated with these traits. Classical quantitative genetics approaches allow study of the genetic architecture of polygenic traits even where the genetic basis of adaptation remains unknown. These approaches have the potential to overcome some of the limitations of previous studies into the genetics and fitness of NTSR. RESULTS: Using a quantitative genetic analysis of 400 pedigreed Alopecurus myosuroides seed families from nine field‐collected populations, we found strong heritability for resistance to the acetolactate synthase and acetyl CoA carboxylase inhibitors ( h 2 = 0.731 and 0.938, respectively), and evidence for shared additive genetic variance for resistance to these two different herbicide modes of action, r g = 0.34 (survival), 0.38 (biomass). We find no evidence for genetic correlations between life‐history traits and herbicide resistance, indicating that resistance to these two modes of action is not associated with large fitness costs in blackgrass. We do, however, demonstrate that phenotypic variation in plant flowering characteristics is heritable, h 2 = 0.213 (flower height), 0.529 (flower head number), 0.449 (time to flowering) and 0.372 (time to seed shed), demonstrating the potential for adaptation to other nonchemical management practices (e.g. mowing of flowering heads) now being adopted for blackgrass control. CONCLUSION: These results highlight that quantitative genetics can provide important insight into the inheritance and genetic architecture of NTSR, and can be used alongside emerging molecular techniques to better understand the evolutionary and fitness landscape of herbicide resistance. © 2022 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : Quantitative genetics reveals the heritability of flowering traits and shared additive‐genetic variance for resistance to the acetolactate synthase and acetyl CoA carboxylase inhibitors, but no evidence for large fitness costs associated with these resistances.